Meeting of Latin America Journals of Obstetrics and Gynecology Editors - Pacheco-Romero, José (2018)
It is known that Peruvian scientific production continues with low indicators when compared to the South American context (1). Research in the regions and at the national level is little promoted and even less funded, and is practically confined to universities and research institutes (2). Only 24% of the projects to obtain the title of specialist of a Peruvian university come to be published (3). And on medical institutions and research and publication, the National Institute of Health published in the article mentioned that of 327 investigations presented at that institution between 2004 and 2008, 182 were approved, 150 executed, 129 (71%) completed and only 18 (10%) published (2). Among others, only 8% of the papers presented at the congresses of the Peruvian Society of Gastroenterology were published (4) (NdelE: The Journal of Gastroenterology of Peru is one of the 2 Peruvian biomedical journals indexed in Medline). There are 37 medical societies registered in the Medical College of Peru. Despite the fact that 31 of 32 medical societies request the presentation of a research project to be associated, only 2 require the publication of at least one research (5).